Dekontruksi Makanan Penutup Apem Menjadi Petit Four Product dalam Sajian Standar Hotel - Listiaty, Tia; Setiawaty, Ety; Irawan, Joseph Aldo; Muhammad Firman Hafidhi (Jurnal Ekonomi, Manajemen Pariwisata dan Perhotelan, 2026)
This research aims to study and deconstruct the traditional Indonesian dish known as kue apem, which becomes a petit four product expected to meet the standards of presentation in star-rated hotels. Apem, as a typical Indonesian dessert, is generally served simply. The deconstruction process includes modifications to the shape, appearance, size, texture, and taste while maintaining the traditional flavors. This research uses research and development (R&D) with a 4D model, namely (define, design, development, and dissemination). The instrument used in data collection is a questionnaire distributed to 25 panelists of lecturers and students of the Prima Internasional Tourism Polytechnic. The trial in this study used hedonic testing, which examines preferences for color, taste, texture, aroma, and appearance. The results of the study show that modifying apem cake into petit four products can enhance their attractiveness. In conclusion, the aspects of color, taste, aroma, texture, and appearance are acceptable to consumers. This study is expected to provide new references for the culinary and hospitality industries.